2015
DOI: 10.1128/genomea.01313-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two South African Bacillus anthracis Strains

Abstract: Bacillus anthracis is a Gram-positive bacterium that causes anthrax, mainly in herbivores through exotoxins and capsule produced on plasmids, pXO1 and pXO2. This paper compares the whole-genome sequences of two B. anthracis strains from an endemic region and a sporadic outbreak in South Africa. Sequencing was done using next-generation sequencing technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…While cluster 4 ( n = 18; Fig. 4B ) contained only isolates classified in the NCBI database as B. anthracis , it contained assemblies from several strains with attenuated virulence, including several vaccine strains ( 62 64 ). Cluster 22 ( n = 5; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While cluster 4 ( n = 18; Fig. 4B ) contained only isolates classified in the NCBI database as B. anthracis , it contained assemblies from several strains with attenuated virulence, including several vaccine strains ( 62 64 ). Cluster 22 ( n = 5; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lethal challenge studies were conducted at a remote site in an endemic area of the Kruger National Park (KNP), South Africa. Animal experiments and clinical score sheets for monitoring experimental animals were drawn up according to the guidelines of the National Research Council of the USA (Clark et al, 1996, 21-34) plasmids, pXO1 and pXO2, was confirmed using real time PCR and sequencing (Lekota et al, 2015(Lekota et al, , 10.1128.…”
Section: Animalsmentioning
confidence: 99%
“…In B. endophyticus 2102, no prophage sequence regions were identified. Comparative analysis of prophages between B. anthracis strains 3631_1C and 20SD [ 14 ] and B. endophyticus sequenced in this study indicated that the four Lambda Ba prophages remain unique to B. anthracis .…”
Section: Resultsmentioning
confidence: 97%
“… a The strains that were subjected for sequencing b Draft genome from previous study [ 14 ] c Kudu 1, kudu 2, sheep 1 etc. refer to different animal carcasses with B. endophyticus (3617_2C) and B. anthracis (3617_1C) isolated from the same kudu carcass (kudu 1) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation